How much “Italianity” in the texts of Polish Italians? Bibliometric notes - Słapek, Daniel (Sperimentare ed esprimere l’Italianità: Aspetti linguistici e glottodidattici, 2021)
The sociology of science treats scientific activity as a given system of relations and social processes. The specific goals of this meta‑scientific discipline include the analysis of grant/funding policy, the bibliometric analysis of academic output, the designation of authorities in a given field, the study of conference/doctoral dissertation topics, etc. In today’s academic reality, representatives of foreign language and literature studies, belonging to different schools and scientific paradigms, constitute a special group. Their research work is difficult because – in practice – they often must reconcile two scientific perspectives/traditions, and their belonging, so to speak, to different scientific paradigms makes the circle of their potential discussants quite limited. In this chapter, I attempt to carry out a bibliometric analysis of the scientific publications written by Polish Italianists in 2019, in terms of their “Italianity”, i.e., belonging to the Italian academic tradition. In the general section, we will see statistics on the language and place of publication, the affiliation of the author in relation to the place of publication, and the cooperation of the authors/editors. The detailed section presents an analysis of the bibliographic references published in the journal articles in terms of the type of publications cited, their language, and their place of publication.